Uma leitura comunitarista de Hannah Arendt - Lopes, Hellen Maria de Oliveira (2019)
This dissertation stablishes the relationship between the philosophical thinking of Hannah Arendt and the communitarian theory. In order to reach this communitarian reading of Hannah Arendt, we analysed her works and we shall present her criticism to modernity understanding that this period has presented itself as mainly liberal. We shall present the depiction of the modern individual that is manifested in its atomized form and alienated in relation to the common affairs of the public arena. We shall analyse starting from this criticism this modern massified individual relating him to the one that served as foundation to the rise of totalitarian regimes. We approached Arendt's analysis about the conflict that exists in the dawn of Social Sphere, refered as a hybrid sphere of private and public affairs. Plus, we analysed the criticism on marxism as a theory that not only enforced the split with the tradition of phylosophical thought but also made possible what Arendt coined animal laborans, the individual that lives for the labour and has as main problem the maintenance of his life in its biological aspects. Starting from this split with the tradition, we exposed the fragility in relation to political action and the morality that ensured the rise of totalitary regimes as the new law of Earth. The rise of those regimes brought to the debate the concept of the banality of evil in Arednt's thought from the judgment of Adolf Eichmann. Against the emergence of a pessimist or nihilist analysis of Hannah Arendt's philosophy we present her concepts that aim to overcome a negative view of historical events through the reflection of reasoning and judgement, just like Amor Mundi. From these concepts, we sought to rebuild the “trust of men in the world” and we shall present the rescue of sensus communis, inauguranting the questions that were part of the tradition with the objective that these might again shed light on the present events, and also allow the reconciling between philosophy and politics – thought and action.